2002
DOI: 10.1002/mc.10046
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of proliferation and expression of T1 and cyclin D1 genes by thyroid hormone in mammary epithelial cells

Abstract: The relationship between thyroid hormone (triiodothyronine, T(3)) and breast cancer is unclear. We studied the effect of the c-erbA/TR alpha proto-oncogene encoding a functional T(3) receptor (TR alpha 1), of its ligand T(3), and of its retroviral, mutated counterpart, the v-erbA oncogene, on the proliferation capacity of nontumorigenic mammary epithelial cells (EpH4). We found that EpH4 cells expressing ectopically TR (EpH4 + TR alpha 1) or v-erbA (EpH4 + v-erbA) proliferated faster than parental EpH4 cells t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 49 publications
0
24
1
Order By: Relevance
“…TRa1 receptor, in the absence of ligand, is now recognised to be implicated in cardiac cell growth (27) and in other tissues in cell proliferation (28), while liganded TRa1 promotes differentiation (29). This could provide an explanation for the fact that cardiac hypertrophy was developed at later stages after myocardial infarction in rats and not as early as 2 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…TRa1 receptor, in the absence of ligand, is now recognised to be implicated in cardiac cell growth (27) and in other tissues in cell proliferation (28), while liganded TRa1 promotes differentiation (29). This could provide an explanation for the fact that cardiac hypertrophy was developed at later stages after myocardial infarction in rats and not as early as 2 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Other work has suggested that T3 increases other CDKIs, such as p16 Ink4a and p18 Ink4c , and this represents another potential mechanism by which T3 could produce effects on Sertoli cell proliferation (Burton et al 1999;Tokumoto et al 1999Tokumoto et al , 2002Ballock et al 2000). Finally, T3 has been shown to effect proliferation in other cell types as a result of changes in the expression of cell cycle proteins such as cyclins D1, D2, or E (Pibiri et al 2001;Gonzalez-Sancho et al 2002;Poguet et al 2003) or of their partners such as Cdk2 (Barrera-Hernandez et al 1999;Huang et al 2002) or Cdk4 (Huang et al 2002), and one or more of these effects could be involved in the T3 effects on Sertoli cell proliferation (Tokumoto et al 2002). Clearly, T3 effects on p27 Kip1 and p21 Cip1 are critical for establishing Sertoli cell number, but other cell cycle proteins may also be targets of T3.…”
Section: Thyroid Hormone Regulates Early Sertoli Cell Developmentmentioning
confidence: 93%
“…However, the presence of thyroid hormone receptors in human breast and breast cancer cell lines has been established (21,22,23,24), and the proliferative effect of T 3 has been confirmed by various experimental studies on breast cancer. Our findings are in line with these data (25,26,27,28).…”
Section: T 3 (Quartile)mentioning
confidence: 99%